2018
DOI: 10.4034/pboci.2018.181.108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gingivitis among Malian Children

Abstract: Objective: To determine the prevalence of gingivitis among Malian children in Bamako, Mali. Material and Methods: This cross-sectional study evaluated 2640 children aged between 3 to 14 years old and two examiners collected the data. The gingival index was used to determine the degree of gingival. Gingival inflammation has been classified localized and / or generalized according to site rate achieved. Descriptive statistics were used to calculate the absolute and relative frequencies. Results: The prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…It was also reported that a high prevalence of gingivitis (87.5%), with a higher incidence among girls (60.6%) than boys (39.5%). 58.2% of students had plaque-induced gingivitis, 67% had moderate gingival inflammation, and 64.7% had localized gingivitis among school students (Kane et al 2018). The previous study's findings are consistent with the current results, demonstrating a higher incidence of gingivitis among females than males.…”
Section: Gingivitissupporting
confidence: 90%
“…It was also reported that a high prevalence of gingivitis (87.5%), with a higher incidence among girls (60.6%) than boys (39.5%). 58.2% of students had plaque-induced gingivitis, 67% had moderate gingival inflammation, and 64.7% had localized gingivitis among school students (Kane et al 2018). The previous study's findings are consistent with the current results, demonstrating a higher incidence of gingivitis among females than males.…”
Section: Gingivitissupporting
confidence: 90%